The Role Of The Family Affecting Patient Care Diabetes Mellitus - Ana Yulianih; Ricky Riyanto Iksan; Sri Atun Wahyuningsih (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2021)
Diabetes mellitus is a serious chronic disease that occurs either when the pancreas does not produce enough insulin, or when the body cannot effectively use the insulin it produces. Diabetes Mellitus is a disease that can increase the threat of health and death of each individual quickly and has great challenges to achieve success in management. This study aims to identify the role of the family in treating Diabetes Mellitus. This research method uses a case study design and consists of four respondents. Data collection was carried out in the Kelurahan Duri Kepa Health Center, Kebon Jeruk District, West Jakarta on 27-31 May 2021 with instruments in the form of interview guidelines, observation guidelines, notebooks, and tools to measure blood sugar levels in patients. The results showed that the application of the intervention of the family role in 4 respondents after being given education and family support the value of the family role was in the good category of 100%. The conclusion in this study the role of the family has shown positive results that can affect the care of patients with diabetes mellitus.